Subprime Crisis and Financial Contagion: Evidence from Tunisia - GHARSELLAOUI, Mongi (International Journal of Economics and Financial Issues, 2012)
The purpose of this paper is to study the subprime crisis while focusing on the phenomenon of financial contagion. Subprime crisis is a crisis that has hit the U.S. mortgage sector and helped to trigger the financial crisis of 2007-2009. In the context of this study, we are interested in exposing the subprime crisis and the contagion first point. The second point will be reserved for the transmission channels of contagion and the third point; we will try to assess the impact of liquidity on the capital market returns. This study shows that the Tunisian financial market does not seem to be very influenced by the subprime crisis. This can be explained by the intrinsic characteristics of the Tunisian market, an underdeveloped market and elemental thing that can make him more or less immune to that crisis. Keywords: Subprime crisis; financial contagion; intrinsic characteristics; capital market returns; Tunisian market JEL Classifications: E60; F30; G01; M31